The Impact of Population Ageing on Public Debt: A Panel Data Analysis for 18 European Countries - Afflatet, Nicolas (International Journal of Economics and Financial Issues, 2018)
Population ageing is one of the major long-term challenges industrialized countries face. Forecasts predict that public debt is going to rise sharply for most countries due to population ageing. However, until now there has been little research on how population ageing already affects public debt. Based on a panel data analysis for 18 European countries it is shown that there is only little empirical evidence for such an impact until 2015. This does certainly not mean that it will not have an effect on public debt in the future. Governments are well-advised to benefit from the breathing space the still moderate total dependency ratio offers to adapt their social security systems. Keywords: Population ageing, public debt, social security systems, demographic dividend JEL Classifications: E62, H63, J11